Modified boron nitride filler, method for preparing same, and epoxy resin composite material

CN122978747APending Publication Date: 2026-10-27NINGBO INST OF TECH ZHEJIANG UNIV ZHEJIANG
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202610829992.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-06-10
Publication Date
2026-10-27

AI Technical Summary

Technical Problem

[0006]本发明要解决的第一个技术问题是提供一种改性氮化硼填料,以解决现有技术中因导热粒子与阻燃剂物理共混导致界面热阻大以及两者功能失调的问题

Benefits of technology

[0008]本发明的一种改性氮化硼填料与现有技术相比,具有以下优点:本发明将现有技术中无机导热粒子与化学阻燃剂简单多组分混合、随机分布的状态,改为以六方氮化硼纳米片为核心并在其表面依次结合聚多巴胺层、铁元素和9,10-二氢-9-氧杂-10-磷杂菲-10-氧化物的有机集成结构,聚多巴胺层凭借其富含的邻苯二酚基团牢固附着于呈惰性的六方氮化硼基体表面,不仅改善了填料表面的亲水性与化学活性,还利用邻苯二酚结构高效螯合具有空轨道的过渡金属铁元素,铁元素作为过渡层进一步充当分子桥梁,与9,10-二氢-9-氧杂-10-磷杂菲-10-氧化物分子中的磷氧基团发生络合配位,从而使阻燃单元均匀、稳固地原位锚定在导热骨架外围,避免了小分子阻燃剂在基体中的无序聚集或受热游离迁移;本发明采用核壳一体化的结构设计,利用聚多巴胺层的介导作用增强了填料与高分子基体之间的化学浸润性,减少了界面处的微观空隙并缓解了应力集中,降低声子失配引发的界面热阻以促进连续导热网络的构建;同时将阻燃单元定向集中于高导热的六方氮化硼表面,使得材料在受热燃烧时,二维片状基体的物理阻隔作用能与外层受热分解产生的气相捕获游离基作用、以及催化周围树脂炭化的凝聚相功能在空间上紧密结合,导热通路转化为高强度的成炭骨架,协同加快了表面致密炭层的构筑,妥善应对了背景技术中所提及的填料易团聚、界面结合力弱以及导热与阻燃单元互相孤立干扰的技术缺陷。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN122978747A_ABST
    Figure CN122978747A_ABST
Patent Text Reader

Abstract

The application belongs to the technical field of polymer composites, and specifically discloses a modified boron nitride filler, a preparation method thereof and an epoxy resin composite. The modified boron nitride filler comprises a hexagonal boron nitride nanosheet matrix, a polydopamine layer self-aggregated on the surface of the matrix, iron elements combined on the polydopamine layer through chelation, and 9,10-dihydro-9-oxa-10-phosphaphenanthrene-10-oxide (DOPO) complexed on the iron elements through a coordination bond. The intermediate layer constructed by polydopamine and iron elements is used as a molecular bridge to deeply integrate the heat-conducting matrix and the flame-retardant unit, effectively improving the interface compatibility of the filler and the resin matrix and reducing the interface thermal resistance. When the filler is introduced into the epoxy resin, the thermal conductivity and the flame-retardant grade of the composite material can be greatly improved at a low filling amount, and excellent comprehensive mechanical properties can be maintained, so that the application prospect in the field of electronic packaging materials and heat dissipation insulation is wide.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of polymer composite materials technology, specifically to a modified boron nitride filler, its preparation method, and an epoxy resin composite material. Background Technology

[0002] Epoxy resins, due to their excellent electrical insulation, chemical corrosion resistance, and superior mechanical properties and processability, have been widely used in modern electronic packaging, coatings, adhesives, and structural composite materials. As microelectronics technology and the semiconductor industry evolve towards higher integration, miniaturization, and higher power density, the heat density generated by electronic components during operation has increased significantly. If this heat cannot be dissipated in time, it will inevitably lead to localized heat accumulation, affecting the operational stability and lifespan of the components. Furthermore, the epoxy resin skeleton is mainly composed of flammable elements such as carbon, hydrogen, and oxygen, and its limiting oxygen index is low. When heated in air, it is highly susceptible to continuous combustion, accompanied by large amounts of dense smoke and heat release, posing a significant safety hazard. Therefore, endowing epoxy resins with high thermal conductivity and good flame retardant properties has become an important issue in the field of electronic packaging.

[0003] Currently, the industry typically employs physical blending, directly filling the epoxy resin matrix with inorganic thermally conductive particles such as hexagonal boron nitride and alumina, or mixing in phosphorus-based and nitrogen-based chemical flame retardants, in an attempt to improve the matrix's properties. However, in actual modification processes, inorganic fillers like hexagonal boron nitride often exhibit strong chemical inertness, resulting in significant differences in chemical structure between them and the organic polymer matrix. This leads to poor interfacial wettability, causing the filler to easily aggregate and agglomerate randomly within the matrix. This not only makes it difficult to construct continuous and efficient thermal conduction pathways but also introduces numerous defects and voids at the interface, generating significant interfacial thermal resistance and limiting the improvement of thermal conductivity.

[0004] Meanwhile, traditional small-molecule flame retardants such as 9,10-dihydro-9-oxa-10-phosphaphenanthrene-10-oxide, while capable of exhibiting certain flame-retardant effects in the gas or condensed phases, often require extremely high addition amounts to achieve high flame-retardant ratings in composite materials. This disrupts the continuity of the polymer matrix and leads to a significant decline in the material's bending and tensile mechanical strength. Furthermore, small-molecule compounds are prone to freeing and migrating to the material surface during long-term service or thermal alteration, reducing the flame-retardant effect and potentially causing secondary pollution of electronic components. Moreover, when thermally conductive fillers and flame-retardant fillers are simply mixed and added in a multi-component manner, the two types of particles with vastly different properties tend to be randomly and disordered in the matrix, lacking organic chemical bonding. This can easily lead to mutual interference between the thermally conductive pathway and the charred flame-retardant skeleton, often resulting in a trade-off between the two, making it difficult to achieve a synergistic improvement in thermal conductivity and flame-retardant performance at low filling amounts.

[0005] Based on the problems existing in the above-mentioned technologies, such as poor interfacial compatibility of inorganic fillers, mutual isolation and interference between thermal conductivity and flame retardant functions, and deterioration of the overall mechanical properties of materials due to excessive filling of flame retardants, there is an urgent need for a new type of functional filler and its composite material that can achieve deep integration of thermal conductivity and flame retardant units and improve the interfacial bonding force with the resin matrix. Summary of the Invention

[0006] The first technical problem to be solved by the present invention is to provide a modified boron nitride filler to solve the problems of high interfacial thermal resistance and functional imbalance caused by the physical blending of thermally conductive particles and flame retardants in the prior art.

[0007] To overcome the shortcomings of the prior art, the present invention provides a modified boron nitride filler, comprising: Hexagonal boron nitride nanosheet matrix; A polydopamine layer is self-polymerized and coated on the surface of the hexagonal boron nitride nanosheet matrix; Iron elements are bound to the polydopamine layer through chelation; and 9,10-dihydro-9-oxa-10-phosphaphenanthrene-10-oxide is complexed with the iron element via coordination bonds.

[0008] Compared with existing technologies, the modified boron nitride filler of this invention has the following advantages: This invention replaces the simple multi-component mixture and random distribution of inorganic thermally conductive particles and chemical flame retardants in existing technologies with an organic integrated structure consisting of hexagonal boron nitride nanosheets as the core, with a polydopamine layer, iron, and 9,10-dihydro-9-oxa-10-phosphaphenanthrene-10-oxide sequentially bonded to their surface. The polydopamine layer, rich in catechol groups, firmly adheres to the inert hexagonal boron nitride matrix surface, improving not only the hydrophilicity and chemical activity of the filler surface but also utilizing the catechol structure to efficiently chelate the transition metal iron with empty orbitals. The iron, as a transition layer, further acts as a molecular bridge, complexing and coordinating with the phospho groups in the 9,10-dihydro-9-oxa-10-phosphaphenanthrene-10-oxide molecule. This allows the flame-retardant units to be uniformly and stably anchored in situ to the thermally conductive matrix. The outer shell structure prevents the disordered aggregation or thermal migration of small molecule flame retardants in the matrix. This invention adopts a core-shell integrated structural design, utilizing the mediating effect of the polydopamine layer to enhance the chemical wettability between the filler and the polymer matrix, reduce microscopic voids at the interface and alleviate stress concentration, and reduce interfacial thermal resistance caused by phonon mismatch to promote the construction of a continuous thermally conductive network. At the same time, the flame retardant units are oriented and concentrated on the highly thermally conductive hexagonal boron nitride surface, so that when the material is heated and burned, the physical barrier effect of the two-dimensional sheet matrix can be spatially combined with the gas phase capturing free radicals generated by the thermal decomposition of the outer layer and the condensed phase function of catalyzing the carbonization of the surrounding resin. The thermally conductive pathway is transformed into a high-strength char-forming skeleton, which synergistically accelerates the construction of a dense char layer on the surface, effectively addressing the technical defects mentioned in the background art, such as easy agglomeration of fillers, weak interfacial bonding, and mutual isolation and interference between thermally conductive and flame-retardant units.

[0009] In one possible implementation, the sheet size of the hexagonal boron nitride nanosheet matrix is ​​1~3 μm.

[0010] In this embodiment, hexagonal boron nitride nanosheets with a size range of 1~3 μm are used. The large aspect ratio of the sheet structure makes it easier for them to overlap and form long-range phonon conduction pathways in the blend system. At the same time, it provides a suitable specific surface area for the self-polymerization and coating of the outer polydopamine and the grafting of subsequent components, preventing the filler from being over-accumulated in the resin matrix and deteriorating the processing flowability due to the small sheet size.

[0011] The second technical problem to be solved by the present invention is to provide a method for preparing modified boron nitride filler, so as to solve the problems of complicated modification process, harsh conditions and weak loading of flame retardant components in the prior art.

[0012] To overcome the shortcomings of the prior art, the present invention provides a method for preparing the modified boron nitride filler, comprising the following steps: S1: Dopamine hydrochloride is dissolved in an alkaline aqueous solution to obtain a mixed system. Hexagonal boron nitride nanosheet powder is added to the mixed system and stirred to react, so that the dopamine hydrochloride self-polymerizes on the surface of the hexagonal boron nitride nanosheet powder to form a polydopamine layer. After solid-liquid separation and washing, BNNS@PDA intermediate is obtained. S2: The BNNS@PDA intermediate obtained in step S1 is dispersed in ferric chloride aqueous solution and stirred at room temperature to allow iron ions to complex onto the polydopamine layer. After solid-liquid separation, washing and drying, BNNS@PDA@Fe composite filler is obtained. S3: The BNNS@PDA@Fe composite filler obtained in step S2 is dispersed in an anhydrous ethanol solution containing 9,10-dihydro-9-oxa-10-phosphaphenanthrene-10-oxide, and a complexation reaction is carried out under heating and stirring. After the reaction is completed, the anhydrous ethanol is removed and the filler is dried to obtain the modified boron nitride filler.

[0013] Compared with existing technologies, the preparation method of the modified boron nitride filler of this invention has the following advantages: The preparation method provided by this invention replaces the complex silane coupling agent modification and multi-step organic synthesis process of existing technologies with a three-step continuous in-situ construction method that sequentially performs self-polymerization, chelation and complexation reactions in a mild aqueous phase and alcohol phase. In step S1, the oxidative self-polymerization characteristics of dopamine molecules under alkaline aqueous phase conditions are utilized to deposit a uniformly coated polydopamine layer on the surface of inert hexagonal boron nitride nanosheets, completing the transformation of the solid surface from hydrophobic to hydrophilic; in step... In step S2, phenolic hydroxyl and amino groups generated on the surface of the polydopamine layer are used to rapidly capture iron ions, and the construction of transition metal coordination centers is completed at room temperature and atmospheric pressure. In step S3, anhydrous ethanol is used as a solvent to provide a homogeneous environment, and under gentle heating, the flame retardant components are guided to approach the metal center and undergo efficient coordination complexation. After the reaction, the solvent is directly removed and dried, avoiding the loss of flame retardant caused by multiple washings. Moreover, it does not rely on expensive reaction equipment, and the raw materials are all industrial products, realizing effective control of the layer thickness and chemical composition of the modified filler.

[0014] In one possible implementation, in step S1, the alkaline aqueous solution is a potassium hydroxide aqueous solution with a pH of 8-9.

[0015] Compared with the prior art, this embodiment controls the pH value of the reaction within the range of 8 to 9, which can ensure that the catechol structure of dopamine undergoes rapid oxidative dehydrogenation and initiates self-polymerization chain growth, while avoiding excessive alkalinity that would cause the dopamine self-polymerization rate to run out of control and generate a large number of free polydopamine particles. This ensures that the polydopamine layer can be uniformly and densely deposited on the surface of hexagonal boron nitride nanosheets.

[0016] In one possible implementation, in step S1, the mass ratio of dopamine hydrochloride to hexagonal boron nitride nanosheet powder is 1:20 to 1:40; in step S2, the mass ratio of ferric chloride to hexagonal boron nitride nanosheet powder is 1:10 to 1:15.

[0017] Compared with the prior art, this embodiment further limits the mass ratio of dopamine hydrochloride to hexagonal boron nitride nanosheet powder and the mass ratio of ferric chloride to hexagonal boron nitride nanosheet powder. This ensures that the amount of dopamine polymerized is just enough to form an ultrathin continuous modification layer with a nanometer-thickness on the surface of hexagonal boron nitride. This provides sufficient active sites for functional groups while avoiding the risk of excessive thermal resistance introduced by an excessively thick organic layer. At the same time, the amount of ferric chloride added is matched with the number of catechol groups on the dopamine layer, so that the introduced iron element can achieve stoichiometric chelation, providing sufficient and uniformly distributed coordination anchors for the subsequent grafting of flame retardants.

[0018] In one possible implementation, in step S3, the heating temperature is 50~70°C and the stirring time is 3~6 hours.

[0019] Compared with existing technologies, the above-mentioned technical solution can provide sufficient random thermal kinetic energy to the small flame retardant molecules in the anhydrous ethanol solution by heating and stirring at 50~70℃, while ensuring that the anhydrous ethanol solvent does not evaporate violently. This overcomes steric hindrance and accelerates the coordination chemical bonding between the flame retardant and the transition metal iron center on the filler surface. Within 3~6 hours, the coordination complexation reaction is more complete, making full use of the coordination sites of the iron element. This ensures that the flame retardant component can be stably loaded and avoids the flame retardant component falling off during subsequent blending and use.

[0020] The third technical problem to be solved by the present invention is to provide an epoxy resin composite material to solve the technical problems of low thermal conductivity and high flammability of conventional epoxy resin materials in the prior art.

[0021] To overcome the shortcomings of the prior art, the present invention provides an epoxy resin composite material, comprising an epoxy resin matrix, a modified boron nitride filler dispersed in the epoxy resin matrix, and a curing agent for curing the epoxy resin matrix; wherein the modified boron nitride filler is the aforementioned modified boron nitride filler.

[0022] In one possible embodiment, the curing agent is 4,4'-diaminodiphenylmethane; the mass ratio of the epoxy resin matrix to the curing agent is 4:1.

[0023] Compared with the prior art, the epoxy resin composite material of the present invention has the following advantages: The epoxy resin composite material provided by the present invention has balanced thermal conductivity and high flame retardancy while maintaining extremely low filler addition. It is constructed by crosslinking network with a specific ratio of aromatic amine curing agent. Furthermore, the modified boron nitride filler with both matrix wettability and spatial binding is introduced into the cured product, which alleviates matrix delamination between inorganic components and polymer. While significantly improving the thermal conductivity and carbon layer density, it ensures that the original three-dimensional crosslinking network of the matrix is ​​not excessively destroyed, resulting in good comprehensive mechanical strength.

[0024] In one possible implementation, the mass percentage of 9,10-dihydro-9-oxa-10-phosphaphenanthrene-10-oxide is 5 wt% to 8 wt%, based on the total mass of the epoxy resin composite material.

[0025] Compared with existing technologies, controlling the mass percentage of 9,10-dihydro-9-oxa-10-phosphaphenanthrene-10-oxide in the epoxy resin composite material to be 5 wt% to 8 wt% enables the flame retardant component to form a uniformly distributed flame retardant network in the resin system, ensuring that the char layer formed when heated can completely cover the matrix surface. While ensuring flame retardant efficiency, it avoids interference with the heat conduction path and matrix continuity caused by an excessively high component proportion.

[0026] In one possible implementation, the mass percentage of 9,10-dihydro-9-oxa-10-phosphaphenanthrene-10-oxide is 6 wt%, based on the total mass of the epoxy resin composite material.

[0027] In this embodiment, the content of 9,10-dihydro-9-oxa-10-phosphaphenanthrene-10-oxide in the epoxy resin composite material is further limited to 6 wt%. At this point, the release rate of the flame retardant component and the carbonization rate of the matrix are well balanced, so that the final epoxy resin composite material can obtain excellent vertical combustion self-extinguishing performance while maintaining a high thermal conductivity. Attached Figure Description

[0028] Figure 1 The images shown are scanning electron microscope (SEM) images of the fillers at each stage of the preparation process in the embodiments of the present invention; wherein, (a) is a scanning electron microscope image of the BNNS@PDA@Fe intermediate, and (b) is a scanning electron microscope image of the BNNS@PDA@Fe-DOPO modified boron nitride filler. Figure 2 Scanning electron microscope (SEM) images of the brittle fracture cross section of the epoxy resin composite material prepared in the embodiments of the present invention; wherein, (a) and (b) are microscopic morphology images of the cross section of the EP / BNNS@PDA@Fe-DOPO composite material at different magnifications; Figure 3 This is a comparison chart of the thermal conductivity of different epoxy resin composite materials prepared in the embodiments and comparative examples of the present invention; Figure 4 This is a comparison chart of the limiting oxygen index test results of different epoxy resin composite materials prepared in the embodiments and comparative examples of the present invention; Figure 5 This is a comparison chart showing the results of different epoxy resin composite materials prepared in the embodiments and comparative examples of the present invention in the UL-94 vertical burning test.

[0029] The meanings of the English abbreviations and codes in the attached figures are as follows: EP is the pure epoxy resin sample prepared in Comparative Example 1; EP / BN is the epoxy resin composite material filled with original inorganic hexagonal boron nitride nanosheets in Comparative Example 2; BNP@Fe-D-1 is the modified boron nitride filler prepared in Example 3, and the corresponding epoxy resin composite material contains 5 wt% 9,10-dihydro-9-oxa-10-phosphaphenanthrene-10-oxide. BNP@Fe-D-2 is the modified boron nitride filler prepared in Example 1, and the corresponding epoxy resin composite material contains 6 wt% 9,10-dihydro-9-oxa-10-phosphaphenanthrene-10-oxide. EP / BNP@Fe-D-2 is the epoxy resin composite material prepared using BNP@Fe-D-2 filler in Example 2; BNP@Fe-D-3 is the modified boron nitride filler prepared in Example 3, and the corresponding epoxy resin composite material contains 7 wt% 9,10-dihydro-9-oxa-10-phosphaphenanthrene-10-oxide. BNP@Fe-D-4 is the modified boron nitride filler prepared in Example 3, and the corresponding epoxy resin composite material contains 8 wt% 9,10-dihydro-9-oxa-10-phosphaphenanthrene-10-oxide. Detailed Implementation

[0030] First, those skilled in the art should understand that these embodiments are merely used to explain the technical principles of the present invention and are not intended to limit the scope of protection of the present invention. Those skilled in the art can make adjustments as needed to adapt to specific applications. In this invention, the proportion of the 9,10-dihydro-9-oxa-10-phosphaphenanthrene-10-oxide to the total mass of the epoxy resin composite material is calculated as: mass of 9,10-dihydro-9-oxa-10-phosphaphenanthrene-10-oxide / (mass of epoxy resin matrix + mass of curing agent + total mass of modified boron nitride filler) × 100%.

[0031] This invention provides a modified boron nitride filler, comprising: Hexagonal boron nitride nanosheet matrix; A polydopamine layer is self-polymerized and coated on the surface of the hexagonal boron nitride nanosheet matrix; Iron elements are bound to the polydopamine layer through chelation; and 9,10-dihydro-9-oxa-10-phosphaphenanthrene-10-oxide is complexed with the iron element via coordination bonds.

[0032] As a preferred embodiment, the sheet size of the hexagonal boron nitride nanosheet matrix is ​​1~3 μm.

[0033] This invention provides a method for preparing the modified boron nitride filler, comprising the following steps: S1: Dopamine hydrochloride is dissolved in an alkaline aqueous solution to obtain a mixed system. Hexagonal boron nitride nanosheet powder is added to the mixed system and stirred to react, so that the dopamine hydrochloride self-polymerizes on the surface of the hexagonal boron nitride nanosheet powder to form a polydopamine layer. After solid-liquid separation and washing, BNNS@PDA intermediate is obtained. S2: The BNNS@PDA intermediate obtained in step S1 is dispersed in ferric chloride aqueous solution and stirred at room temperature to allow iron ions to complex onto the polydopamine layer. After solid-liquid separation, washing and drying, BNNS@PDA@Fe composite filler is obtained. S3: The BNNS@PDA@Fe composite filler obtained in step S2 is dispersed in an anhydrous ethanol solution containing 9,10-dihydro-9-oxa-10-phosphaphenanthrene-10-oxide, and a complexation reaction is carried out under heating and stirring. After the reaction is completed, the anhydrous ethanol is removed and the filler is dried to obtain the modified boron nitride filler.

[0034] As a preferred embodiment, in step S1, the alkaline aqueous solution is a potassium hydroxide aqueous solution with a pH value of 8-9.

[0035] As a preferred embodiment, in step S1, the mass ratio of dopamine hydrochloride to hexagonal boron nitride nanosheet powder is 1:20 to 1:40; in step S2, the mass ratio of ferric chloride to hexagonal boron nitride nanosheet powder is 1:10 to 1:15.

[0036] As a preferred embodiment, in step S3, the heating temperature is 50~70℃ and the stirring time is 3~6 hours.

[0037] The present invention provides an epoxy resin composite material, comprising an epoxy resin matrix, a modified boron nitride filler dispersed in the epoxy resin matrix, and a curing agent for curing the epoxy resin matrix; wherein the modified boron nitride filler is the aforementioned modified boron nitride filler.

[0038] As a preferred embodiment, the curing agent is 4,4'-diaminodiphenylmethane; the mass ratio of the epoxy resin matrix to the curing agent is 4:1.

[0039] As a preferred embodiment, the 9,10-dihydro-9-oxa-10-phosphaphenanthrene-10-oxide in the epoxy resin composite material has a mass percentage content of 5 wt% to 8 wt%.

[0040] As a preferred embodiment, the 9,10-dihydro-9-oxa-10-phosphaphenanthrene-10-oxide in the epoxy resin composite material has a mass percentage content of 6 wt%.

[0041] The modified boron nitride filler of this invention alters the original inert surface properties of inorganic particles by coating a composite layer of polydopamine and iron onto the surface of hexagonal boron nitride nanosheets and complexing and grafting 9,10-dihydro-9-oxa-10-phosphaphenanthrene-10-oxide onto the outer layer. The polydopamine layer improves the interfacial wettability between the filler and the epoxy resin matrix, allowing the filler to be uniformly dispersed and tightly bound within the resin at lower addition levels, reducing interfacial voids and lowering interfacial thermal resistance, which is beneficial for constructing continuous heat conduction pathways. Simultaneously, utilizing the transitional binding effect of iron, small-molecule flame-retardant components are stably loaded onto the filler surface, avoiding the tendency of flame retardants to aggregate and react during heating, as is common in traditional physical blending modifications. The problem of blooming due to migration is beneficial to maintaining the stability of flame retardant performance. When the composite material is heated and burned, the two-dimensional lamellar boron nitride, which serves as a thermally conductive skeleton, can be spatially tightly combined with the gas-phase flame retardant effect generated by the decomposition of the outer flame retardant components and the catalytic carbonization function. This allows the thermally conductive pathway to simultaneously act as a char-forming barrier channel, accelerating the formation of a dense char layer on the surface. Thus, with a lower total filler content, it balances the improvement of thermal conductivity and vertical combustion self-extinguishing performance, while avoiding the degradation of the original tensile, bending, and other mechanical properties of the epoxy resin matrix caused by high filler content. The filler is prepared in aqueous and alcohol phases under mild reaction conditions and stable process steps. The raw materials are all commercially available products, demonstrating good production feasibility and industrial application prospects.

[0042] The following are embodiments incorporating specific data to further elaborate on the above-described technical solutions of the present invention: Example 1 This embodiment provides a modified boron nitride filler and its preparation method. The specific preparation steps are as follows: S1: Dissolve 0.2 g of dopamine hydrochloride in 100 mL of deionized water and stir for 15 min to obtain a mixed system. Quickly add 8.44 mL of 1 mol / L KOH solution to the mixed system to adjust the pH to alkaline. Stir the reaction to activate it. Then add 6 g of hexagonal boron nitride nanosheet powder with a sheet size of 1~3 μm to the mixed system and stir continuously at room temperature for 12 h to allow dopamine hydrochloride to self-polymerize on the surface of hexagonal boron nitride nanosheet powder to form a polydopamine layer. After the reaction is completed, centrifuge at 8000 rpm for 10 min and wash with deionized water to obtain BNNS@PDA intermediate. S2: Dissolve 0.54 g FeCl3·6H2O in 40 mL of deionized water to construct a ferric chloride aqueous solution. Add all of the BNNS@PDA intermediate obtained in step S1 to the ferric chloride aqueous solution and stir the reaction at room temperature for 2 h to allow iron ions to complex onto the polydopamine layer. After the reaction is completed, centrifuge at 8000 rpm for 10 min, wash with deionized water and dry to obtain the BNNS@PDA@Fe composite filler. S3: 3.55 g of 9,10-dihydro-9-oxa-10-phosphaphenanthrene-10-oxide was dissolved in 40 mL of anhydrous ethanol solution and stirred in an oil bath at 60°C for 30 min. Then, 5.56 g of the BNNS@PDA@Fe composite filler obtained in step S2 was added. The complexation reaction was carried out at 60°C with magnetic stirring for 4 h. After the reaction, the anhydrous ethanol was removed by rotary evaporation at 65°C and the mixture was dried to obtain the target modified boron nitride filler, denoted as BNP@Fe-D-2. This filler, when used in subsequent composite material preparation, meets the requirement of the required proportion of 9,10-dihydro-9-oxa-10-phosphaphenanthrene-10-oxide in the total mass of the epoxy resin composite material.

[0043] Example 2 This embodiment provides an epoxy resin composite material and its preparation method. In Example 2, the modified boron nitride filler BNP@Fe-D-2 obtained in step S3 of Example 1 is used for compounding. The specific steps are as follows: Weigh 40 g of epoxy resin matrix and heat it to 80°C. Add the modified boron nitride filler BNP@Fe-D-2 obtained in step S3 of Example 1 to it and maintain stirring at 80°C for 30 min. Then transfer it to a vacuum drying oven for degassing. Add 10 g of curing agent 4,4'-diaminodiphenylmethane to the degassed system and maintain stirring until the curing agent is completely dissolved and presents a homogeneous phase. Transfer it to a vacuum drying oven again for secondary degassing. Pour the homogeneous mixture into a preheated mold while it is still hot and send it into a forced-air drying oven. Cure it at 120°C for 2 hours, then raise the temperature to 160°C and continue curing for 3 hours. After the system cools naturally, demold it to obtain the epoxy resin composite material, denoted as EP / BNP@Fe-D-2. Based on the total mass of the epoxy resin composite material prepared in this embodiment, the mass percentage of 9,10-dihydro-9-oxa-10-phosphaphenanthrene-10-oxide is approximately 6 wt%.

[0044] Example 3 This embodiment provides a set of modified boron nitride fillers, their preparation methods, and corresponding epoxy resin composite materials. This embodiment is similar to Embodiments 1 and 2, except that in step S3, the initial mass of 9,10-dihydro-9-oxa-10-phosphaphenanthrene-10-oxide was changed and then introduced into the epoxy resin matrix, so that the proportion of 9,10-dihydro-9-oxa-10-phosphaphenanthrene-10-oxide in the total mass of the epoxy resin composite material was 5 wt%, 7 wt%, and 8 wt%, respectively. The corresponding modified fillers were designated as BNP@Fe-D-1, BNP@Fe-D-3, and BNP@Fe-D-4, respectively. Subsequently, the above three modified fillers were introduced into the epoxy resin matrix according to the same material ratio and curing modification process as in Embodiment 2, and the corresponding epoxy resin composite materials were prepared and labeled as EP / BNP@Fe-D-1, EP / BNP@Fe-D-3, and EP / BNP@Fe-D-4, respectively.

[0045] Comparative Example 1 This comparative example provides a pure epoxy resin material as a blank control group. The difference between this material and Example 2 is that no modified boron nitride filler is added during the preparation of the resin composite material. 40 g of epoxy resin matrix and 10 g of curing agent 4,4'-diaminodiphenylmethane are directly mixed and stirred at 80°C until completely dissolved and degassed. The homogeneous mixture is then poured into a mold while hot and the specimen is formed in accordance with the two-stage thermosetting process in Example 2. Finally, a pure epoxy resin specimen, denoted as EP, is obtained.

[0046] Comparative Example 2 This comparative example provides an unmodified boron nitride-filled epoxy resin composite material as a performance comparison group. The difference between this and Example 2 is that the modified boron nitride filler of this invention is not used in the preparation of the resin composite material. Instead, 5.56 g of raw hexagonal boron nitride nanosheet powder without any surface chemical modification is directly added to 40 g of epoxy resin matrix. The mixture is stirred at 80°C for 30 min and degassed. Then, 10 g of curing agent 4,4'-diaminodiphenylmethane is added, and the subsequent blending, secondary degassed and two-stage thermal crosslinking curing process is completed in strict accordance with the method of Example 2. The final resin composite material is denoted as EP / BN.

[0047] Characterization and performance evaluation: The microstructure and physical properties of the filler intermediates, final target fillers, and epoxy resin composite material samples prepared in the above embodiments and comparative examples were characterized and tested. The microstructure of the filler material at each stage was observed using a scanning electron microscope, such as... Figure 1 As shown, Figure 1 Figure (a) shows the surface features of the BNNS@PDA@Fe composite filler prepared in step S2 of Example 1. It can be seen that the micron-scale two-dimensional sheet surface exhibits a slight roughness due to the self-polymerization deposition of polydopamine and the chelation of iron. Figure 1 Figure (b) shows the surface morphology of the target modified boron nitride filler obtained after the complexation reaction in step S3. Compared with the intermediate, its lamellar surface and edges are significantly thickened and have a uniform functional coating layer attached, confirming that the flame-retardant small molecules have been successfully grafted onto the molecular bridge constructed by iron and polydopamine.

[0048] Figure 2 The scanning electron microscope (SEM) image of the brittle fracture section of the epoxy resin composite EP / BNP@Fe-D-2 prepared in Example 2 is shown. Figure 2 (a) and Figure 2 (b) At two different magnifications, it can be observed that the modified filler exhibits a uniform and non-agglomerated dispersion within the epoxy resin matrix, and the edges of the inorganic sheets of the filler are tightly bonded to the organic resin matrix. No obvious peeling voids or mechanical cracks appear at the interface, indicating that the polydopamine coating layer on the surface effectively improves the chemical wettability and compatibility between the inorganic particles and the epoxy resin matrix.

[0049] Further tests were conducted on the thermal conductivity, limiting oxygen index (LOI), and UL-94 vertical flammability rating of each group of composite material samples. The specific test results are recorded in Table 1 below: Table 1 Performance test results of different samples Combination Figure 3 , Figure 4 and Figure 5 Analyzing the evolution trend of the physical properties reflected, the pure epoxy resin in Comparative Example 1 exhibits extremely high flammability due to its inherent molecular chain composition. Its thermal conductivity is only 0.200 W / (m·K), and it is accompanied by severe melting and dripping during vertical combustion, making it impossible to obtain a flame retardant rating. In Comparative Example 2, after directly filling with the original inorganic boron nitride, the thermal conductivity was slightly improved to 0.328 W / (m·K), but the objective existence of interface defects limited the further leap in thermal conductivity efficiency, and it also could not achieve self-extinguishing in the vertical combustion test.

[0050] In contrast, the epoxy resin composite material provided in Example 2 of this invention, while maintaining a low filler content, significantly improves its thermal conductivity to 0.481 W / (m·K), representing a 140.5% increase compared to pure resin. Its limiting oxygen index rises dramatically to 42.6%, and it exhibits excellent flame retardant response rate in vertical burning tests. The first self-extinguishing time t1 after flame removal is only 3.2 seconds, and the second self-extinguishing time t2 is 1.8 seconds. No dripping ignition behavior occurred during the entire test, successfully achieving the high standard flame retardant level of UL-94 V-0. Furthermore, data comparison from Example 3 shows that controlling the total mass percentage of 9,10-dihydro-9-oxa-10-phosphaphenanthrene-10-oxide in the epoxy resin composite material within the range of 5 wt% to 8 wt% can play a balancing and harmonizing role in the overall thermal conduction pathway and charring barrier of the condensed phase in the final material. Specifically, setting this total percentage at 6 wt%... At wt% (as shown in Example 2), the composite material achieves an excellent kinetic match between thermal conductivity and flame-retardant self-extinguishing behavior, exhibiting the best comprehensive modification effect.

[0051] In summary, this invention achieves chemical integration of thermally conductive and flame-retardant units through a modification path that sequentially combines polydopamine, iron, and flame-retardant components on the surface of hexagonal boron nitride nanosheets. The experimental data show that directly filling with unmodified boron nitride results in poor compatibility with the resin interface, leading to microscopic defects in the matrix and limited improvement in thermal conductivity, while failing to address the flammability issue of epoxy resin. Using the modification scheme of this invention, with the total mass of the epoxy resin composite material as the baseline, controlling the mass percentage of 9,10-dihydro-9-oxa-10-phosphaphenanthrene-10-oxide within the range of 5 wt% to 8 wt% effectively balances the thermal conductivity and flame-retardant behavior of the material. In particular, when the content of 9,10-dihydro-9-oxa-10-phosphaphenanthrene-10-oxide is 6 wt%, the effect is even better. At wt%, the modified filler is uniformly dispersed in the resin matrix. The gas-phase quenching effect released by the outer flame-retardant components and the polydopamine-mediated char formation of the condensed phase work together to improve the thermal conductivity of the final epoxy resin composite material while maintaining low filler content and good mechanical strength, and achieve the UL-94 V-0 flame retardant standard. This demonstrates the practical value of the modified filler of this invention in improving the overall performance of epoxy resin.

[0052] In the description of this invention, the terms "one embodiment," "some embodiments," "in this embodiment," "specific example," or "some examples," etc., refer to specific features, mechanisms, materials, or characteristics described in connection with that embodiment or example, which are included in at least one embodiment or example of the invention. In this specification, the illustrative expressions of the above terms do not necessarily refer to the same embodiment or example. Furthermore, the specific features, mechanisms, materials, or characteristics described may be combined in any suitable manner in one or more embodiments or examples. Moreover, without contradiction, those skilled in the art can combine and integrate the different embodiments or examples described in this specification, as well as the features of different embodiments or examples.

[0053] The above description is merely a specific embodiment of the present invention, but the scope of protection of the present invention is not limited thereto. Any variations or substitutions that can be easily conceived by those skilled in the art within the technical scope disclosed in the present invention should be included within the scope of protection of the present invention. Therefore, the scope of protection of the present invention should be determined by the scope of the claims.

Claims

1. A modified boron nitride filler, characterized in that, include: Hexagonal boron nitride nanosheet matrix; A polydopamine layer is self-polymerized and coated on the surface of the hexagonal boron nitride nanosheet matrix; Iron elements are bound to the polydopamine layer through chelation; and 9,10-dihydro-9-oxa-10-phosphaphenanthrene-10-oxide is complexed with the iron element via coordination bonds.

2. The modified boron nitride filler according to claim 1, characterized in that, The sheet size of the hexagonal boron nitride nanosheet matrix is ​​1~3 μm.

3. A method for preparing the modified boron nitride filler as described in claim 1 or 2, characterized in that, Includes the following steps: S1: Dopamine hydrochloride is dissolved in an alkaline aqueous solution to obtain a mixed system. Hexagonal boron nitride nanosheet powder is added to the mixed system and stirred to react, so that the dopamine hydrochloride self-polymerizes on the surface of the hexagonal boron nitride nanosheet powder to form a polydopamine layer. After solid-liquid separation and washing, BNNS@PDA intermediate is obtained. S2: The BNNS@PDA intermediate obtained in step S1 is dispersed in ferric chloride aqueous solution and stirred at room temperature to allow iron ions to complex onto the polydopamine layer. After solid-liquid separation, washing and drying, BNNS@PDA@Fe composite filler is obtained. S3: The BNNS@PDA@Fe composite filler obtained in step S2 is dispersed in an anhydrous ethanol solution containing 9,10-dihydro-9-oxa-10-phosphaphenanthrene-10-oxide, and a complexation reaction is carried out under heating and stirring. After the reaction is completed, the anhydrous ethanol is removed and the filler is dried to obtain the modified boron nitride filler.

4. The preparation method according to claim 3, characterized in that, In step S1, the alkaline aqueous solution is a potassium hydroxide aqueous solution with a pH value of 8-9.

5. The preparation method according to claim 3, characterized in that, In step S1, the mass ratio of dopamine hydrochloride to hexagonal boron nitride nanosheet powder is 1:20 to 1:40; in step S2, the mass ratio of ferric chloride to hexagonal boron nitride nanosheet powder is 1:10 to 1:

15.

6. The preparation method according to claim 3, characterized in that, In step S3, the heating temperature is 50~70℃ and the stirring time is 3~6 hours.

7. An epoxy resin composite material, characterized in that, The method includes an epoxy resin matrix, a modified boron nitride filler dispersed in the epoxy resin matrix, and a curing agent for curing the epoxy resin matrix; wherein the modified boron nitride filler is the modified boron nitride filler according to claim 1 or 2.

8. The epoxy resin composite material according to claim 7, characterized in that, The curing agent is 4,4'-diaminodiphenylmethane; the mass ratio of the epoxy resin matrix to the curing agent is 4:

1.

9. The epoxy resin composite material according to claim 7, characterized in that, In the epoxy resin composite material, the 9,10-dihydro-9-oxa-10-phosphaphenanthrene-10-oxide accounts for 5 wt% to 8 wt% of the total mass of the epoxy resin composite material.

10. The epoxy resin composite material according to claim 9, characterized in that, The 9,10-dihydro-9-oxa-10-phosphaphenanthrene-10-oxide accounts for 6 wt% of the total mass of the epoxy resin composite material.